Recombinant thrombomodulin for acute exacerbation in idiopathic interstitial pneumonias. Issue 7 (5th March 2019) - Arai, Toru; Kida, Hiroshi; Ogata, Yoshitaka; Marumo, Satoshi; Matsuoka, Hiroto; Gohma, Iwao; Yamamoto, Suguru; Mori, Masahide; Sugimoto, Chikatoshi; Tachibana, Kazunobu; Akira, Masanori; Edahiro, Ryuya; et al.
ABSTRACT: Background and objective: Acute exacerbation (AE) in idiopathic pulmonary fibrosis (IPF) or other idiopathic interstitial pneumonias (IIP) is a poor prognostic event despite conventional therapy with corticosteroids and/or immunosuppressants. We aimed to evaluate the efficacy and safety of recombinant human soluble thrombomodulin (rhTM) for AE‐IIP. Methods: For this prospective single‐arm open‐label multicentre cohort study, we retrospectively registered 61 cases of AE‐IIP treated with conventional therapy between 2011 and 2013 (control arm), and prospectively enrolled 39 cases of AE‐IIP treated with conventional therapy and rhTM (380 U/kg/day for 6 days) between 2014 and 2016 (rhTM arm). To reduce potential confounding in treatment comparisons, an adjusted mortality analysis for 90‐day survival was conducted with weighted Cox proportional hazards regression models using inverse probability of treatment weighting. Weights were derived from propensity scores estimated using a multivariable logistic regression analysis including potential confounders. Results: The 90‐day survival rates of AE‐IIP patients treated with/without rhTM were 66.7% (26/39) and 47.5% (29/61), respectively. After adjusting for imbalances, rhTM therapy was significantly associated with reduced mortality (adjusted hazard ratio (HR): 0.453; 95% CI: 0.237–0.864; P = 0.0163). The frequencies of adverse events with/without rhTM were 17.9% (7/39) and 19.7% (12/61), which were similar in both arms ( P = 1.0). Two bleeding‐related adverse events occurred in the rhTM arm. Conclusion: Safety and efficacy were observed for rhTM treatment of AE‐IIP. A future randomized controlled trial is required to draw final conclusions. Abstract : Our prospective single‐arm open‐labelled multicentre study aimed to evaluate the efficacy and safety of recombinant human soluble thrombomodulin (rhTM) treatment for acute exacerbation in idiopathic interstitial pneumonias (AE‐IIP). rhTM therapy was significantly associated with reduced mortality due to AE‐IIP after a propensity score adjustment. Similar frequencies of adverse events with/without rhTM were noted. See related Editorial